Experimental investigation on the thermal performance of three-dimensional vapor chamber for LED automotive headlamps. (5th July 2019) - Lu, Zhimin; Bai, Pengfei; Huang, Bin; Henzen, Alex; Coehoorn, Reinder; Liao, Hua; Zhou, Guofu
Highlights: A 3D VC with an integrated structure for LED automotive headlamps was fabricated. The thermal performance of the 3D VC under different conditions was tested. The lowest measured thermal resistance is 0.125 °C/W at 50 W. Abstract: This paper proposes a three-dimensional vapor chamber (3D VC) to solve heat dissipation of LED (light-emitting diode) automotive headlamps, which can be installed in a very limited setup space and a high heating load. The proposed 3D VC can be regarded as a combination of a flattened heat pipe and a circular vapor chamber. A test system was implemented to study the effects of different heating modes on thermal performance, power distribution characteristics, the temperature distribution and thermal resistance of the 3D VC. The experimental results show that the thermal performance of the 3D VC by both-sides heating is better than that of the one-side heating under the same total heating load. The 3D VC exhibits a favorable temperature uniformity, and the minimum thermal resistance of the 3D VC is 0.125 °C/W at a 50 W heating load.